The role of the communist party in article 4 of the 2013 constitution of Vietnam - Cam, Thi Lai (Đại học Quốc gia Hà Nội, 2020)
The paper analyses the theoretical and practical basis of the new regulations on the position, and responsibilities of the Communist Party in Article 4 of the 2013 Constitution of the Socialist Republic of Vietnam. Besides, the author also raises issues and requirements set out in the implementation of these regulations in Vietnam nowadays. The research questions that the author tries to answer in this article include: (1) How does the Article 4 of the 2013 Constitution of the Socialist Republic of Vietnam (talking about the Communist Party of Vietnam (herein after CPV1 ) differ from those of the previous Constitution? (2) What are the theoretical and practical basis of the new points included in Article 4 of the 2013 Constitution? (3) What are the requirements for implementing Article 4 of Vietnam’s 2013 Constitution?